RANCANG BANGUN MONITORING PENGGUNAAN AIR DAN ESTIMASI TAGIHAN PDAM BERBASIS INTERNET OF THINGS (IOT) - Ramadhani , Lalu Thoriq; Darmawan, budi; wrindi, Warindi (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING, INFORMATION TECHNOLOGY, CONTROL ENGINEERING, AND ROBOTIC), 2023)
Water is a very important source of life for survival on earth. Clean water services are generally carried out by the Regional Drinking Water Company (PDAM) which is distributed to each resident's house. The meter functions to measure and record how much debit has been used for the needs of each household. In addition customers feel that there is no cost transparency and cannot estimate the amount of fees that must be paid each month. The purpose of this study was to produce a system for monitoring PDAM water use and billing using the NodeMCU ESP8266 with the YF-S201 sensor. This digital water meter hardware is designed using a water flowmeter sensor (YF-S201) which will read the debit of water flowing from the customer's water meter, the results of reading the water flowmeter sensor in the form of pulses then by NodeMCU ESP8266 it becomes an accumulative debit with units of Volume Liters and Volume. Cubic meter. Displays on the LCD and on Telegram are in the form of flow, total liters, total cubic meters and costs. From the test results Based on the analysis of 10 samples the YF S201 sensor has the highest error of 3.00% and the lowest is 0.33% and the average error is 1.53% so that the accuracy of the YF-S201 sensor is 98%.